2023
DOI: 10.1021/acsami.3c05928
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Cu Species in Fe-MOFs on Fenton-Like Catalytic Activity and Stability

Abstract: Fe-based MOFs (Fe-MOFs) are deemed promising Fenton-like catalysts due to their well-developed pores and accessible active sites. However, their inferior catalytic activity, iron leaching, and low H2O2 utilization always hinder their application as Fe-based MOF catalysts. In this work, we manipulated the structure of Fe-oxo nodes in MIL-88B(Fe) via a CuI species substitution method, affording a mixed-valence (Cu-incorporated Fe-MOFs) with highly improved Fenton-like performance. It is found that the CuI serves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…In recent years, peroxidase-like mimics have also been intensively employed in the field of advanced oxidative degradation of various pollutants in addition to sensing. , In particular, Fe-based MOF materials can act as Fenton-like catalysts to promote hydrogen peroxide to rapidly generate a large number of free radicals, so as to achieve efficient oxidative degradation of pollutants. To expand the application of Fe–Co-MOFs, the Fenton-like catalytic degradation properties of Fe–Co-MOFs were exploited in this section.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In recent years, peroxidase-like mimics have also been intensively employed in the field of advanced oxidative degradation of various pollutants in addition to sensing. , In particular, Fe-based MOF materials can act as Fenton-like catalysts to promote hydrogen peroxide to rapidly generate a large number of free radicals, so as to achieve efficient oxidative degradation of pollutants. To expand the application of Fe–Co-MOFs, the Fenton-like catalytic degradation properties of Fe–Co-MOFs were exploited in this section.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Tang et al [97] accomplished the degradation of ibuprofen by anchoring ReS 2 nanoparticles in a heterojunction formed in MIL-88B (Fe) under visible light and persulfate (PS). Song et al [98] obtained mixed-valent Cu@MIL-88B(Fe) after processing the Fe-oxo node structure in MIL-88B(Fe) by the Cu + species substitution method. Both experimental and computational results showed that Cu + played a shuttling role in promoting the transfer between Fe 2+ /Fe 3+ and inducing the formation of a large number of stable Fe 2+ sites, as well as suppressing the leaching of iron ions during the catalytic process.…”
Section: Photo-fenton Systemmentioning
confidence: 99%